2017
DOI: 10.14738/abr.51.2368
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Non-Performing Loans in Nigerias Deposit Money Banks

Abstract: The study examines the relationship between bank specific and macroeconomic determinant of non-performing loans in Nigerian deposit money banks over the period of 5 years (2010 to 2014). A sample of 10 banks out of 15 quoted by the Nigerian Stock Exchange (NSE) was considered on a cross sectional basis. The study adopted non-survey research design and secondary data was used, generated from the bank's annual reports and accounts, Central Bank of Nigeria (CBN) and Nigerian Stock Exchange fact book respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 3 publications
2
14
1
4
Order By: Relevance
“…El-Maude [2] examined the relationship and influence of specific factors of banks and macroeconomics on NPLs in 10 commercial banks in Nigeria during the period 2010 to 2014. Injuries suffered due to bad credit losses have reduced the capital position of many banks, which can cause the Nigerian banking industry's failure.…”
Section: Literatur Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…El-Maude [2] examined the relationship and influence of specific factors of banks and macroeconomics on NPLs in 10 commercial banks in Nigeria during the period 2010 to 2014. Injuries suffered due to bad credit losses have reduced the capital position of many banks, which can cause the Nigerian banking industry's failure.…”
Section: Literatur Reviewmentioning
confidence: 99%
“…It indicates that rural banks have not been optimal in managing their assets, making them vulnerable to liquidation. Risk assets such as total loans are a significant part of bank assets [2]. As a financial institution with the main activity of collecting and distributing funds, rural banks are faced with credit risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPL as percentage of total loans, which is represented by the empirical results in cases of SCBs, is very high and they hold greater than 50% of the total NPLs of the banking industry during last 8 years. Study was conducted by another researchers such as, Akinlo and Emmanuel (2014) on the determinants of non-performing loan with a macroeconomic model in the banking system of Nigeria. It has been found that economic growth is negatively related to non-performing loan.…”
Section: Page13 Page13 Page13mentioning
confidence: 99%
“…NPL as percentage of total loans, which is represented by the empirical results in cases of SCBs, is very high and they hold greater than 50% of the total NPLs of the banking & financial industry during the last 8 years. Study was conducted by Akinlo and Emmanuel (2014) on the determinants of non-performing loan with a macroeconomic model in the banking system of Nigeria. It has been found that economic growth is adversely integrated with the non-performing loan.…”
Section: Literature Reviewmentioning
confidence: 99%